Resilience Thinking: Sustaining Ecosystems and People in a Changing Wo rld - Walker, Brian; Salt, David; Reid, Walter V. (Island Press, 2006)
Increasingly, cracks are appearing in the capacity of communities, eco systems, and landscapes to provide the goods and services that sustain our planet's well-being. The response from most quarters has been for "more of the same" that created the situation in the first place: mor e control, more intensification, and greater efficiency. "Resilience t hinking" offers a different way of understanding the world and a new a pproach to managing resources. It embraces human and natural systems a s complex entities continually adapting through cycles of change and s eeks to understand the qualities of a system that must be maintained o r enhanced in order to achieve sustainability. It explains why greater efficiency by itself cannot solve resource problems and offers a cons tructive alternative that opens up options rather than closing them do wn. In "Resilience Thinking", scientist Brian Walker and science write r David Salt present an accessible introduction to the emerging paradi gm of resilience. The book arose out of appeals from colleagues in sci ence and industry for a plainly written account of what resilience is all about and how a resilience approach differs from current practices . Rather than complicated theory, the book offers a conceptual overvie w along with five case studies of resilience thinking in the real worl d. It is an engaging and important work for anyone interested in manag ing risk in a complex world.